Community perceptions of mental illness in rural Uganda: An analysis of existing challenges facing the Bwindi Mental Health Programme - Arya Shah; Lydia Wheeler; Kristen Sessions; Yusufu Kuule; Edwin Agaba; Stephen P. Merry (AOSIS, 2017)
Objectives: To assess community perceptions of mental illness in the Bwindi Community Hospital (BCH) catchment area: to recognise beliefs about the causes and the treatments for mental illness. To provide community data to staff at BCH as they work to develop more effective community mental health programmes. Background: A shortage of mental health providers in Uganda has prompted research into community-based task-sharing models for the provision of mental health services in underserved communities. Methods: Six focus group discussions, with a total of 54 community members (50% male, n = 27; mean age + s.d. [39.9 + 10.9 years]) from the BCH catchment area, were conducted to assess community member and stakeholder perceptions of mental illness and belief in the feasibility of community-based programming. Qualitative study of data through thematic analysis was conducted to assess the presence of commonly occurring perceptions. Results: Qualitative thematic analysis revealed two major themes: (1) belief that any given patient's metal illness results from either an intrinsic or an extrinsic cause and (2) belief in a need to determine treatment of mental illness based on the believed cause. Conclusion: As BCH designs community-based mental health services, our findings provide support for the need for further education of community members and training of community health workers to address and integrate the above-stated beliefs regarding mental illness.